2016
DOI: 10.1002/anzf.1184
|View full text |Cite
|
Sign up to set email alerts
|

Family Therapy for Adolescents: A Research‐informed Perspective

Abstract: Specific research‐informed models of family therapy have been developed for a range of adolescent problems. These include Brief Strategic Family Therapy (BSFT), Functional Family Therapy (FFT), Multisystemic Therapy (MST), Multidimensional Family Therapy (MDFT), and Multidimensional Treatment Foster care (MTFC) for conduct disorder and drug misuse; family‐focused cognitive behaviour therapy for anxiety disorders and depression; Attachment‐based Family Therapy (ABFT) for depression; family‐focused therapy as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…This study's findings that the dose‐response effect found in rural adolescents can elevate the risk of suicide in adolescents and that LBC suffering from poverty and who experience frequent peer bullying are particularly vulnerable to suicidal behaviour could inform the development of appropriately targeted suicide prevention programs and have strong implications for clinical practice as they underscore the importance of screening for suicidal behaviours in youth who present psychotic‐like symptoms. Research has found that dysfunctional schemas may arise from these adverse social environments (Garety et al, 2001); therefore, cognitive behavioural therapy (Mei et al, 2021; Stafford et al, 2013) or family therapy (Carr, 2016) could be effective psychotherapy approaches to assist adolescents reduce the risk of developing full‐blown psychosis or indulging in suicidal behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings that the dose‐response effect found in rural adolescents can elevate the risk of suicide in adolescents and that LBC suffering from poverty and who experience frequent peer bullying are particularly vulnerable to suicidal behaviour could inform the development of appropriately targeted suicide prevention programs and have strong implications for clinical practice as they underscore the importance of screening for suicidal behaviours in youth who present psychotic‐like symptoms. Research has found that dysfunctional schemas may arise from these adverse social environments (Garety et al, 2001); therefore, cognitive behavioural therapy (Mei et al, 2021; Stafford et al, 2013) or family therapy (Carr, 2016) could be effective psychotherapy approaches to assist adolescents reduce the risk of developing full‐blown psychosis or indulging in suicidal behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…: A critical review of treatments for children and adolescents autorstwa Petera Fonagy'ego i współpracowników, którzy na ponad 600 stronach bardzo szczegółowo odnoszą się do skuteczności poszczególnych form leczenia dzieci i młodzieży w określonych sytuacjach klinicznych [8]. Równie ciekawe i bardziej syntetyczne ujęcie skuteczności oddziaływań rodzinnych dla populacji dzieci i młodzieży proponuje Alan Carr w swoich systematycznych przeglądach [10,11]. W tych dotyczących terapii rodzin z 2014 i 2016 roku można przeczytać o skuteczności: [za 10, 11]: programów behawioralnych dla rodzin w leczeniu zaburzeń snu u dzieci oraz wczesnodziecięcych zaburzeń jedzenia; wielu krótko-i długoterminowych interwencji rodzinnych w zaburzeniach więzi; CBFT (Cognitive Behavioural Family Therapy), MST (Multisystemic Therapy), terapii interakcji rodzic-dziecko w leczeniu następstw przemocy; behawioralnych treningów dla rodziców dzieci z trudnościami w zachowaniu; programów multimodalnych w leczeniu ADHD (farmakoterapia + terapia rodzin lub trening dla rodziców); krótkiej strategicznej terapii rodzin, terapii funkcjonalnej, multisystemowej i MDFT (Multidimensional Family Therapy) w leczeniu zaburzeń zachowania oraz w leczeniu nastolatków używających substancji psychoaktywnych; Family-Based CBT w zaburzeniach lękowych; Attachment-Based Family Therapy (ABFT), Child-Focused CBT i terapii interpersonalnej w zaburzeniach depresyjnych; ABFT, MST i terapii dialektyczno-behawioralnej (DBT) połączonej z terapią wielorodzinną w pracy z nastolatkami z ryzykiem samobójczym; połączenia terapii rodzin z interwencjami indywidualnymi w pracy z żałobą; Psycho-Educational Family Therapy w pracy z pacjentami z ChAD i pierwszym epizodem psychozy; terapii rodzin z nastolatkami samookaleczającymi się, terapii rodzin w modelu Maudsley w zaburzeniach jedzenia; programów rodzinnych w trudnościach z niekontrolowaną cukrzycą -różnych w zależności od wieku dziecka.…”
Section: Kontekst Naukowo-badawczyunclassified
“…La identificación de los factores protectores y de riesgo son de vital importancia para el diseño de investigaciones enfocadas en programas de intervención que permitan modificar los riesgos y fortalecer las características que contribuyen positivamente a la no manifestación de sintomatología del TC y TDAH (Beckman, Janson, y von Kobyletzki, 2016;Carr, 2016;Hassink-Franke, Oud, y Beeres, 2015;Stein, Hans, y Nana-yakkara, 2015). Las conductas agresivas expresadas por los niños es un problema de tipo social de relevancia en la actualidad, que debe ser atendido por profesionales idóneos en diversos campos del conocimiento.…”
Section: Introductionunclassified